THE IMPLEMENTATION OF HUMAN RIGHTS PROTECTION IN INTERNATIONAL INVESTMENT: A STUDY OF THE PROTECTION OF LANDOWNERS' HUMAN RIGHTS IN THE MANDALIKA SPECIAL ECONOMIC ZONE - L Muhammad Rizaldy (Department of Law, Faculty of Law, University of Mataram, 2025)
ABSTRACTThe study's purpose is to identify and analyze the problems of Kuta Mandalika residents who are affected by the Mandalika Special Economic Zone development project. The main legal issue is analyzing the implementation of Human Rights protection in International Investment which is based on the case of landowners' rights in the Mandalika Special Economic Zone. This study's type of research is normative-empirical legal research using a Statute Approach, a case approach, or a conceptual approach. The implementation of human rights protection in international investment activities in the Mandalika Special Economic Zone does not apply the ESF standard based on the FPIC principle resulting in problems in (i) the implementation of meaningful consultation in the socialization of the Mandalika Special Economic Zone project development plan with the community; (ii) the implementation of involuntary resettlement that does not comply with the affected community's needs; (iii) the provision of fair compensation to the affected community; (iv) errors in the census people data of recipients who got recovery assistance; and (v) threats and criminalization of residents whose demonstrations demand relocation and fair compensation. These problems arise because PT. ITDC did not implement meaningful consultation thoroughly with the community to ensure the economic, social, and cultural needs of the affected community.Keywords: Human Rights, Infrigement, Meaningful consultation